Perlindungan Hak Asasi Manusia Pekerja Migran Di Qatar Terhadap Sistem Kafala Berdasarkan Konvensi International Labour Organization Nomor 143 Tahun 1975 Tentang Pekerja Migran - Azarya Gerry Likumahua; Arman Anwar; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Migrant workers have human rights that must be respected and protected.Purposes of the Research: This paper aims to find out and analyze the regulations on the protection of the human rights of migrant workers in terms of ILO Convention Number 143 of 1975 concerning migrant workers and to find out and analyze the kafala system in Qatar contrary to ILO Convention Number 143 of 1975 concerning migrant workers.Methods of the Research: The method used is a normative juridical research method using a case approach and a statutory approachResults of the Research: The results of the study show that the ILO Convention 143 of 1975 concerning Migrant Workers has guaranteed the respect and protection of the human rights of migrant workers, while the Kafala system is based on the Qatar Constitution which is based on Islamic sharia law where the legal relationship between the employer (insurer) and the worker (insured) must be mutually agreed upon. in the contract (agreement) in the principle of trust (sponsorship) imbued with the spirit of religiosity, but in practice its implementation has been misused by employers and companies for the benefit of their personal gain so that they are no longer trustworthy in carrying out their responsibilities as stipulated in the Kafalah system. The Kafala system needs to be reviewed and evaluated by the Government of Qatar so that in its application it is no longer misused. Meanwhile, the ILO needs to provide a firm response to the occurrence of human rights violations of migrant workers in Qatar so that they do not happen again in the future.